2017
DOI: 10.1039/c6ta08170c
|View full text |Cite
|
Sign up to set email alerts
|

Improved electro-grafting of nitropyrene onto onion-like carbon via in situ electrochemical reduction and polymerization: tailoring redox energy density of the supercapacitor positive electrode

Abstract: International audienceHerein, we report a improved method for the physical grafting of 1-nitropyrene (Pyr-NO2) onto highly graphitized carbon onion. This is achieved through a lowering of the onset potential of the pyrene polymerization via in situ reduction of the NO2 group. The additional redox activity pertaining to the reduced NO2 enables exceeding the faradaic capacity which is associated with the p-doping of the grafted pyrene backbone, as observed for pyrene, 1-aminopyrene, and unreduced Pyr-NO2. Theore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…On the other hand, C ad Pyr and C ad PAc show slightly lower capacities of 17 mAh/g. The advantage of such low‐levels of functionalization is they will not hamper the power characteristics of the resulting MWCNT/polymer composites as shown previously, [21] however the capacities remain too low for practical applications. One strategy to enhance the functionalization yield is in‐situ electropolymerization, by dissolving the monomers directly in the electrolyte of the battery, [21,22] (Protocol 2, see experimental section).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…On the other hand, C ad Pyr and C ad PAc show slightly lower capacities of 17 mAh/g. The advantage of such low‐levels of functionalization is they will not hamper the power characteristics of the resulting MWCNT/polymer composites as shown previously, [21] however the capacities remain too low for practical applications. One strategy to enhance the functionalization yield is in‐situ electropolymerization, by dissolving the monomers directly in the electrolyte of the battery, [21,22] (Protocol 2, see experimental section).…”
Section: Resultsmentioning
confidence: 83%
“…The advantage of such low‐levels of functionalization is they will not hamper the power characteristics of the resulting MWCNT/polymer composites as shown previously, [21] however the capacities remain too low for practical applications. One strategy to enhance the functionalization yield is in‐situ electropolymerization, by dissolving the monomers directly in the electrolyte of the battery, [21,22] (Protocol 2, see experimental section). However, this requires many cycles, [21,22] before the maximum capacity can be reached, as seen in Figure S14 for the PPrAc/MWCNT system which requires 200 cycles before doubling the initial capacity of the MWCNT electrode.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The main advantage of this approach is that the redox potential of the monomer can be tuned between 3.5 and 4.5 V vs. Li + /Li, depending on the nature of the utilized pyrene substituents. [62][63][64] It was also shown that the Li + source does not need to be an electron conductor, hence, a low-cost, airstable and a non-soluble inorganic base, Li 3 PO 4 , which plays a key role on scavenging the protons released by pyrene, was proposed. Thus, the combination of pyrene and Li 3 PO 4 together with the AC in the positive electrode successfully pre-lithiated a carbon black based LIC.…”
Section: Pyrene-li 3 Po 4 Based Cascade-type Methodsmentioning
confidence: 99%